Turkish and North American engineering programs: a comparative study of curricular emphases on mathematics, basic sciences, humanities and social sciences - Bilsel, A.; Oral, O.; Pillai, J. (IEEE transactions on education, 1998)
The state of mathematics, basic sciences, humanities and social sciences in Turkish engineering schools are compared with that in North American schools, as exemplified by electrical engineering. The emphasis on mathematics and basic sciences is strong at Turkish universities relative to North American universities, but the tendency to teach as many courses as possible in the core subject has resulted in a complete neglect of the humanities and social sciences. These differences may have significant long-term implications, in the context of globalization, for both the personal development of engineers and the educational and technological progress of the countries concerned.